Preliminary analysis of positive and negative syndrome scale in ketamine-associated psychosis in comparison with schizophrenia - Xu, Ke (J Psychiatr Res, 2014)
OBJECTIVE: Studies of the effects of the N-methyl-D-aspartate (NMDA) glutamate receptor antagonist, ketamine, have suggested similarities to the symptoms of schizophrenia. Our primary goal was to evaluate the dimensions of the Positive and Negative Syndrome Scale (PANSS) in ketamine users (acute and chronic) compared to schizophrenia patients (early and chronic stages). METHOD: We conducted exploratory factor analysis for the PANSS from four groups: 135 healthy subject administrated ketamine or saline, 187 inpatients of ketamine abuse; 154 inpatients of early course schizophrenia and 522 inpatients of chronic schizophrenia. Principal component factor analyses were conducted to identify the factor structure of the PANSS. RESULTS: Factor analysis yielded five factors for each group: positive, negative, cognitive, depressed, excitement or dissociation symptoms. The symptom dimensions in two schizophrenia groups were consistent with the established five-factor model (Wallwork et al., 2012). The factor structures across four groups were similar, with 19 of 30 symptoms loading on the same factor in at least 3 of 4 groups. The factors in the chronic ketamine group were more similar to the factors in the two schizophrenia groups rather than to the factors in the acute ketamine group. Symptom severities were significantly different across the groups (Kruskal–Wallis χ(2)(4) = 540.6, p < 0.0001). Symptoms in the two ketamine groups were milder than in the two schizophrenia groups (Cohen’s d = 0.7). CONCLUSION: Our results provide the evidence of similarity in symptom dimensions between ketamine psychosis and schizophrenia psychosis. The interpretations should be cautious because of potential confounding factors.